Evaluation of metabolic changes in oxalate-rich plant Rumex obtusifolius L. caused by ion beam irradiation - Miyagi, Atsuko (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.